Output regulation via trajectory tracking for chemical reactors with jacket dynamics. (January 2023) - Nguyen, T. Sang; Hoang, N. Ha; Tan, C.K.; Hussain, M.A.; Bonvin, D.
Abstract: This work deals with a control strategy to regulate homogeneous reaction systems in reactors equipped with a cooling jacket. The reaction system is expressed in terms of vessel extents and viewed as a single-input (the inlet coolant temperature), two-output (the reactor and jacket temperatures) plant. The proposed strategy enforces trajectory tracking and ensures zero-error tracking between the two outputs and their time-varying references. Once the reactor temperature reference is set, the other reference is inferred using the heat-transfer equation, which generates a feedback law to adjust the inlet coolant temperature and stabilizes the reactor at the desired equilibrium point. The approach is illustrated on a free-radical polymerization reaction system that exhibits steady-state multiplicity. Highlights: Chemical reactors with jacket dynamics are viewed as single-input two-output plants. Controller design for output regulation of a plant with output multiplicity. The resulting controller relies more on measurements and less on kinetic model. Control performance is assessed by comparison with I&I-based and PI controllers. The proposed controller is robust against measurement noise and model uncertainties.